Breaking the fast: Meal patterns and beliefs about healthy eating style are associated with adherence to intermittent fasting diets - Potter, C; Griggs, R; Brunstrom, J; Rogers, P (Elsevier, 2018)
Many believe that eating three meals each day is healthy and that skipping meals can be detrimental. What remains unclear is whether this belief undermines attempts to restrict energy intake by skipping meals. In an online survey, participants (N = 312) with experience of intermittent fasting (IF) reported their beliefs about healthy meal and snack frequency, as well as their non-fasting-dasy and fasting-day eating patterns. They also reported their level of concern with fasting-day meal patterns and their concern to generate fullness when selecting foods. Individuals currently following an IF diet (Current-IF dieters) and those who had previously attempted an IF diet but were non-adherent (Former-IF dieters) took part. Former-IF dieters were more likely to believe that it is healthy to eat three meals a day, punctuated by several snacks. On fasting-days, Former-IF dieters were also more likely to eat breakfast, a mid-morning snack, lunch, and a mid-afternoon snack whereas Current-IF dieters tended to save their eating for dinner and a late evening snack. Former-IF dieters were also more likely to be concerned about the negative consequences of missing a meal, to eat in anticipation of future hunger, and to prioritise fullness over taste when selecting foods. These findings reveal how beliefs about a healthy eating style can play an important role in shaping dietary patterns. Interventions aimed at modifying beliefs about healthy meal patterns may promote IF diet adherence.